If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = 4(x + -2) + 18 Reorder the terms: 10 + 3x = 4(x + -2) + 18 Reorder the terms: 10 + 3x = 4(-2 + x) + 18 10 + 3x = (-2 * 4 + x * 4) + 18 10 + 3x = (-8 + 4x) + 18 Reorder the terms: 10 + 3x = -8 + 18 + 4x Combine like terms: -8 + 18 = 10 10 + 3x = 10 + 4x Add '-10' to each side of the equation. 10 + -10 + 3x = 10 + -10 + 4x Combine like terms: 10 + -10 = 0 0 + 3x = 10 + -10 + 4x 3x = 10 + -10 + 4x Combine like terms: 10 + -10 = 0 3x = 0 + 4x 3x = 4x Solving 3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = 4x + -4x Combine like terms: 3x + -4x = -1x -1x = 4x + -4x Combine like terms: 4x + -4x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 4x^2+10x-24=0 | | -2x+5=-x+13 | | x^4y^7-x^9y^2= | | 0=12x^2-36x+27 | | 2x-3=25 | | 3(1-3n)=3n+63 | | g(x)=(x+2)-4 | | xy+3=y | | x+2y=3xy | | xy+y=1 | | 12x+6y=18 | | -2x-9=9 | | 6(3x-2)+4x= | | 5(y+6)+4= | | 2x+15=8x+8 | | 6x+16=21 | | 9m-3=-39+3m | | 6(x-1)+4=3(7x+1) | | 5(2t-3)+4t=30-t | | 4y-3=0+y | | 15x^2-34x+15= | | (-3)-(2)= | | 5p+3=4p+6 | | 20p-2p+4p=20p-6p | | -17x-20=14x+70 | | -4x-11x=-75 | | 2.5x+3=15-1.5x | | 2x+1=4x-15 | | 2x-7=x+6 | | 17-5x=9+3x | | 5x+9=2x+30 | | 2x^2-x+6=0 |